Influence of Ta2O5 on the electrical properties of ZnO- and CoO-doped SnO2 varistors - Filho, F. M.; Simoes, A. Z.; Ries, A.; Silva, I. P.; Perazolli, L.; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Elsevier B.V., 2004)
SnO2-based varistors doped with 0.5% cobalt, 0.5% zinc and various tantalum amounts were prepared by the solid-state route. Experimental evidence shows that small quantities of Ta2O5 improve the nonlinear properties of the samples significantly. It was found that samples doped with 0.05 mol% Ta2O5 exhibit the highest density (98.5%), the lowest electric breakdown field (E-b = 1050 V/cm) and the highest coefficient of nonlinearity (alpha = 11.5). The effect of Ta2O5 dopant could be explained by the substitution of Ta5+ by Sn4+. (C) 2004 Elsevier Ltd and Techna S.r.l. All rights reserved.
Keywords: powders : solid state reaction; varistors; tin dioxide